Bentuk Perlindungan Hukum Bagi Pencipta Lagu Dalam Menghadapi Pelanggaran Hak Cipta - Firmansyah, Mochamad Arsyi; Rosando, Abraham Ferry (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Copyright is part of intellectual property rights that provide legal protection to creators for original works they produce, including songs. In today's digital era, copyright infringement of songs is increasingly common, especially through sites that provide free song download services without permission. This study aims to examine the forms of legal protection available to songwriters in dealing with copyright infringement, as well as the effectiveness of law enforcement in Indonesia. The approach used is a normative juridical analysis with respect to laws and regulations such as Law Number 28 of 2014 concerning Copyright and a study of copyright infringement cases in the digital realm. The results of the study indicate that legal protection for songwriters has been strictly regulated, both through preventive protection (creation registration, licenses, and cooperation contracts) and repressive (civil lawsuits and criminal charges). However, implementation in the field still faces challenges, especially in terms of supervision and law enforcement against illegal sites. Therefore, synergy between the government, law enforcement officers, and public awareness is needed to ensure that the rights of songwriters are optimally protected.